2011
DOI: 10.1007/s00417-011-1902-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of experimental porous silicone implants and porous silicone implants

Abstract: Porous silicone orbital implants demonstrated a comparable extent of fibrovascular ingrowth to that for porous polyethylene implants. Therefore, this new porous silicone sphere implant may be a good candidate to substitute for current porous implants at a lower cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The connecting channels allowed the ingrown tissues to extend to adjacent cavities (Figure 8), and they also ensure oxygen exchange and nutrients supply of cells and neo‐tissues within the scaffolds. Previous long‐term clinic observation showed that coralline hydroxyaptite (HA) implant, with porosity of over 80%, displayed the most rapid vascularization, second, the synthetic HA (with a porosity of 50–65%), third, the Medpor (with porosity of about 41%) implants, 1,30‐32 and the last, the porous silicone implant 13 . In addition to the surface chemistry, porosity was probably another critical factor in inducing vascularization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The connecting channels allowed the ingrown tissues to extend to adjacent cavities (Figure 8), and they also ensure oxygen exchange and nutrients supply of cells and neo‐tissues within the scaffolds. Previous long‐term clinic observation showed that coralline hydroxyaptite (HA) implant, with porosity of over 80%, displayed the most rapid vascularization, second, the synthetic HA (with a porosity of 50–65%), third, the Medpor (with porosity of about 41%) implants, 1,30‐32 and the last, the porous silicone implant 13 . In addition to the surface chemistry, porosity was probably another critical factor in inducing vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…The four rectus muscles were detached from their insertions with 6–0 traction sutures. After severing the optic nerve, the eyeball was extracted and meticulous hemostasis was performed 13 . A 15 mm diameter porous silicone sphere was placed into the empty socket, and the remaining rectus muscles stumps were attached to the implant slightly anterior to their normal insertion sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrovascular ingrowth into porous implants offers the potential for excellent prosthesis movement, and also reduces a chance of infection, exposure, and displacement, porous polyethylene, silicon, aluminum oxide have been used. Silicone is a material being used in medical science for variety of prosthetic applications, because of its excellent biocompatibility and low cost, some limitations of silicone are limited ingrowth but it can be improve with the introduction of functional groups or nanoparticles in its surface [13].…”
Section: Porous Materials On Implantsmentioning
confidence: 99%
“…Studies on silicone implants to restore volume in an anophthalmic socket are rare. 1,2 However, cohesive silicone implants are widely used for cosmetic breast augmentation surgery. 3 Controversy remains on whether to use textured or polyurethane-coated silicone implants.…”
Section: Introductionmentioning
confidence: 99%